The Health Effort in Combating Health Problem Areas in Maluku Barat Daya - Putro, Gurendro; Wibowo,; Erlan, Ahmad (International Journal of Current Innovations in Advanced Research, 2023)
Health problem areas (HPA) assistance is carried out to assist districts in changing the planning process in the health sector which is carried out specifically based on available resources. The aim of the study was to determine whether the intervention encouraged the reform of planning, policies, programs and activities to improve the health condition of the HPA region. This study was carried out in all HPA areas assisted by the MoH, an operational research with explorative research, the research population was all institutions health in Southwest Maluku District, the target was chosen purposively. Health Budget in Southwest Maluku District in 2013 was derived from the Regional Expenditure Budget (APBD) of Southwest Maluku Regency and the State Budget (APBN). The Regional Expenditure Budget (APBD) in 2013 allocated funds of Rp. 24,223,253,656. Health human resources in Southwest Maluku Regency are health workers who are divided into 7 groups of health professionals, nurses and midwives, pharmacy, nutritionist, medical technicians, sanitation and public health. The seven groups were spread throughout Puskesmas, Hospitals and Health Offices. Medical personnel (civil servant doctors and internship doctors) numbered 13 people and spread to mobile hospitals and health centers. In addition to medical personnel, there were also other personnel such as 47 midwives and 162 nurses. 7 people in public health, 10 people in public health, 18 people in sanitation, 3 people in pharmacy, 1 person in pharmacy, 1 person in nutrition, 22 people in nutrition college. Health financing can run a health program, although it is still found health problems in the field. There are still many health resources with diploma education, health facilities in the form of hospitals are still damaged in their buildings, they are still very broad and in the form of islands, so that difficulties in reaching all regions.